Os três famosos problemas gregos: uma proposta de introdução à álgebra moderna para o ensino médio integrado do IFAL - Souza, Max Manoel Lima de (2020)
In this work, we bring a project to algebraic learning at IFAL, Murici campus, which has the resolution of three famous greek problems. It comes from the contents covered in high school, agroecology and agroindustry courses. These mathematical problems consists in searching a possible construction of a square that has the same area as a given circle, a angle which is a third of measure of any given other angle, and nally, a cube which volume is the double of another given cube, only with a scale with no markings and a bow compass required.